COGNITIVE AND COMMUNICATIVE PRINCIPLES IN BANGKA MALAY TABOO LANGUAGES - Darmawan, I Nyoman Pasek; Rozani, Muhammad; Afifulloh, M (English Review: Journal of English Education, 2025)
Taboo language within the Malay Bangka community acts as a social boundary that regulates behaviors, preventing discomfort or negative outcomes. This study explores the underlying codes and principles behind the use of taboo language in this community, using Sperber and Wilson's Relevance Theory (1995) to discuss Cognitive and Communicative Principles. The primary data comes from the Bangka Malay community across Bangka and South Bangka Regencies, while secondary sources include various literary works. Data were gathered through listening (simak), interviews (cakap), and document analysis, and were examined using six steps of qualitative analysis. Triangulation was applied to ensure validity, with discussions involving traditional Malay culture experts (Lembaga Adat Melayu). The results of the study suggest that, based on the Cognitive and Communicative Principles, speakers use ostensive stimuli (i.e. particular signals or cues that are deliberately used to indicate that someone is trying to convey information), such as coded phrases like "nanti bengkak kemaluan" (your genital may swell), to guide listeners toward the intended message, ensuring optimal relevance. Additionally, urban myths, often attributed to supernatural forces like ghosts, are employed to reinforce the consequences of disobedience. From the lens of Relevance Theory, these phrases are effective, as they require minimal cognitive effort for listeners to understand and process the speaker’s message.